¿Niña o niño? la incertidumbre del sexo y el género en la infancia - Alcántara, Eva (El Colegio de México A.C., 2016)
It is notable the increasing interest and quandary surrounding issues of sex and gender during the first years of life. In this paper we analyzed three cases in which the childhood is intertwined with modern discourses of sex and gender. The changes of the conditions in which the sexual identity is produced are exposed. Scientific research regarding sex, psychological theories of gender development, the politics that are gradually opening spaces to different possibilities of citizenship, human rights movements and the dissemination of new narratives through the media, are just a few elements that nowadays reconfigure the questions and answers about who and what is a boy or a girl.